Postmortem microcomputed tomography (micro‐CT) of small fetuses and hearts. (13th October 2014) - Lombardi, C. M.; Zambelli, V.; Botta, G.; Moltrasio, F.; Cattoretti, G.; Lucchini, V.; Fesslova, V.; Cuttin, M. S.
ABSTRACT Objective To assess the feasibility and utility of contrast‐enhanced microcomputed tomography (micro‐CT) for identifying structural anomalies in ex‐vivo first‐ and second‐trimester human fetuses and isolated fetal hearts. Methods Radiopaque iodine staining and micro‐CT scanning protocols were first developed in rodent studies and then used to examine routinely fixed whole human fetuses (n = 7, weight 0.1–90 g, gestational age, 7–17 weeks) and isolated fetal hearts (n = 14, weight 0.1–5.2 g, gestational age, 11–22 weeks). Samples were scanned using an isotropic resolution of 18 (and, if necessary, 9 or 35) µm and findings were interpreted jointly by four fetal pathologists, a fetal cardiologist and a radiologist. Samples with gestational ages ≥ 13 weeks also underwent conventional autopsy or dissection. Results Micro‐CT identified all anatomical structures and abnormalities documented by the macroscopic examination. In all seven cases involving fetuses ≤ 13 weeks (four fetuses, three isolated hearts), micro‐CT excluded the presence of structural anomalies. In the remaining 14 cases, it provided all the information obtained with invasive autopsy or dissection and in seven of the 14 (two fetuses, five isolated hearts) it furnished additional diagnostic details. Conclusions This pilot study confirms the feasibility of postmortem contrast‐enhanced micro‐CT assessment of structural anomalies in whole small fetuses and fetal hearts. Further study is needed to confirm our findings, particularly in whole fetuses, and to define the extent to which this virtual examination might be used instead of conventional invasive autopsy. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.